Isolated pericardial echinococcosis: Perioperative transesophageal echocardiographic evaluation - Dogra, Neeti (2013)
Hydatid cyst (HC) is a human parasitic disease caused by the larval stage of Echinococcus granulosus. Cardiac involvement is rare and occurs in 0.5%–2% of patients with hydatid cyst, but isolated pericardial hydatid cyst is rarer still. We present two cases of isolated pericardial hydatid cyst who presented with precordial chest pain and dyspnea. In both the cases, HC were diagnosed by transthoracic echo (TTE), Computed Tomography/Magnetic Resonance and positive hydatid serology. Intraoperatively transesophageal echo (TEE) revealed unilocular transitional cystic lesion the transverse pericardial sinus in one case and multilobulated active cystic lesion in another. The report highlights the role of TEE in diagnosis and evaluation of cardiac HC. Both the cases underwent surgical resection followed by albendazole therapy to prevent recurrence.